Effect of a biopolymer on the mechanical and microstructural behaviour of oil well cement for CO2 geological storage - Barría, Juan Cruz (2021)
Storing CO2 in deep underground reservoirs is key to reducing emissions to the at-mosphere and standing against climate change. However, the risk of CO2 leakage from geological reservoirs to other rock formations requires a careful long-term analysis of the system. Essentially, oil well cement used for the operation must withstand the carbonation process that changes its poromechanical behaviour over time, possibly affecting the system’s integrity. The use of nanoadditives for cement, such as bacterial nanocellulose (BNC), has been increasing in recent years. This biopolymer has particular properties, like high mechanical properties and thermal resistance, that can improve cement performance. For this reason, and in light of the problems that carbonation may pose in the long term in the context of geological storage of CO2, studies were carried out under supercritical CO2 conditions analyzing the behaviour of cement with nanocellulose additions. Rheological, mechanical, thermal, and microstructural tests were performed on samples with different percentages (0%, 0.05%, 0.10%, 0.15%, 0.20%) of bacterial nanocellulose (BNC). 11 free fluid and 6 thickening-time tests were performed to characterize the slurry with BNC. The mechanical behaviour of the hardened state was investigated through the dynamical mechanical analysis (DMA) of 20 samples, measurements of 32 elastic ultrasound waves, 84 unconfined compressive strength (UCS) and 24 triaxial experiments (20 isotropic and 4 compressive tests). A total of 64 cylindrical specimens were subjected to supercritical CO2 conditions (20 MPa and 90 °C) for 30 and 120 days with several percentages of nanocel- lulose using two curing methods, one long-term curing at low temperature (36 specimens) and one short-term curing at high temperature (32 specimens). The microstructure and crystalline characterization were studied by means of thermogravimetric analysis (TGA) of 9 samples, mercury intrusion porosimetry (MIP) of 52 samples, water porosity of 60 samples, scanning electron microscopy (SEM) of 6 samples, and X-ray diffraction (XRD) of 10 samples. These results showed that BNC produces an increase in slurry viscosity but retains a greater amount of water which aids in its subsequent hydration. This could be observed in its microstructure, where a higher degree of hydration, and a decrease in porosity were observed. This increase in hydration was likely the reason why cements with nanocellulose had a uniaxial compressive strength up to 20% higher than neat cement. It was also observed that higher BNC contents improve the thermo-mechanical behaviour under oscillating bending stress. After carbonation, the microstructure shows that the capillary porosity decreases steadily to values of 5%, which reduces the penetration of carbonic acid into the sample. All cements showed a reduction in mechanical strength, but cements with BNC had a lower degree of ii carbonation and better mechanical behaviour, because of the lower capillary porosity prior to carbonation. However, these effects were not observed when the cement was subjected to a curing process under unfavorable conditions at high temperatures. In this case, the large increase in porosity dulls the short-term hydration effects, and the strength of cements with nanocel-lulose is lower than neat cement prior to the carbonation process. After carbonation, a relative increase in the strength of the specimens with BNC is higher, however, it is still below the strength of neat cement. These experimental studies were simulated using a coupled chemo-hydro-mechanical model. The model simulates the carbonation front advance in cement subjected to super- critical CO2 and the changes generated by the chemical reactions using the classic balance equations of porous continua based on conservation of mass and momentum. Simultaneous dissolution of portlandite and C-S-H, dissolution of calcite, and a damage model were added to the existing code. The carbonation progress of the specimens was represented and extrapolation was made to an oil well based on the parameters obtained from the experiments and simulations.